Approaches to the Formation of the Readiness of the Leading Teacher in Younger Schoolchildren - D. K, Tajbenova (European Journal of Life Safety and Stability (2660-9630), 2023)
This article discusses possible approaches to the formation of the readiness of the future teacher.